Mineral Precipitation on Modern Siliciclastic Tidal Flats Colonized by Microbial Mats - Cuadrado, Diana Graciela (2012)
The preservation and cementation of sedimentary structures under the influence of  microorganisms in siliciclastic environments have been poorly studied in contrast to carbonatic settings, where they have been extensively investigated. Whereas in carbonatic environments, microbial mat-induced precipitation of calcium carbonate results in a cementation process producing a quick lithification, in siliciclastic environments other minerals would act as cement. The focus of this paper is to document the presence of authigenic minerals within a biosedimentary fabrics and the possible link of these minerals with the extensive microbial mats that colonize the tidal flat of the temperate Bahía Blanca estuary. ?Anoxic? minerals (e.g. pyrite) and authigenic zeolites such as analcime, clinoptilolite, mordenite, phillipsite and chabazite were recognized through SEM and EDX analyses. These minerals were most likely formed by alteration of volcanic ash, which is present in this tidal flat and also silica may result from dissolution of frustules of benthic diatoms. Minerals precipitated in this setting are significant as they would act as early cement in the eogenesis, enhancing the preservation of sedimentary and biogenic structures.